Metformin Inhibits N-Methyl-N-Nitrosourea Induced Gastric Tumorigenesis in db/db Mice - Zhuang, Shan; Jian, Yongmei; Sun, Yongning (Experimental and Clinical Endocrinology & Diabetes, 2017)
Type 2 diabetes can elevate risk of gastric cancer and metformin, an anti-diabetic agent, has an inhibitory effect against gastric cancer cell in vitro. However, the effect of metformin on type 2 diabetes-related gastric tumorigenesis in vivo is still not clear. In the present study, we aim to detect whether metformin can inhibit increased risk of gastric cancer in diabetic db/db mice and which the potential anti-cancer mechanisms of metformin are. 4-week-old mice were divided into 3 groups (2 db/db mice groups and one wild type mice group). All diabetic and non-diabetic mice were treated with N-Methyl-N-Nitrosourea (MNU) for 20 weeks to induce gastric tumorigenesis. At week 21, one db/db mice group were treated with metformin (5 mg/ml) for 10 weeks and the other 2 groups were treated with saline. Blood samples were collected for testing insulin and insulin-like growth factor (IGF)-1. Stomach tissues were collected for histopathological evaluation and mRNAs analysis. Metformin significantly decreased incidence of MNU-induced gastric dysplasia and cancer in diabetic db/db mice. Furthermore, metformin reduced serum insulin as well as IGF-1, and also suppressed expression of insulin receptor, IGF-1, IGF-1 receptor and several pro-inflammatory cytokines mRNAs in stomach of db/db mice, but did not significantly influence IGF-2 and IGF-2 receptor expressions. The results show that metformin can prevent the risk of gastric cancer in type 2 diabetes and the protective mechanisms may involve in an inhibitory effect of metformin on insulin as well as IGF-1 signals and cancer related pro-inflammatory cytokines.
Keywords: diabetes; gastric cancer; metformin; insulin